KEBIJAKAN PEMBANGUNAN PERKANTORAN BHAKTI PRAJA KABUPATEN PELALAWAN - Tohid Mahrifatullah; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The study, entitled the development policy of Bhakti Praja office in the district of Pelalawan. Policy is a set of decisions that will be right for guidance in the implementation of activities or programs that have been specified. At Bhakti Praja Office construction, certainly use a anvil of policy as a guideline to development implementation, because of a policy that can be seen for what it really such development should be implemented as well as a reference to stages the process. However, in the policy implementation, it often occurs the problems that make hamper the policy. Discussion on development policy Bhakti Praja Office is interesting to study because it will be able to know from the beginning development and become a background in this research. So the authors formulate the problem with the question are how the Government policy district of Pelalawan at the development Bhakti Praja office and what is the factors that become an obstacle development implementation policy at Bhakti Praja office and what the causes of problems at the construction Bahkti Praja Office in the district of Pelalawan.The research method is qualitative with descriptive research, the data collection is done by observation, interviews and documentation. From the results of this research shows that for a policy there must be: 1) Policy Formulation Process, 2) Options and Policy Designation, 3) Policy Implementation, 4) Evaluation of Policy Implementation, and the factors inhibiting the development of Bhakti Praja Offices are: 1) Development Budget, 2) Planning is not optimal to Realized, 3) development Allocation who had uneven, 4) Monitoring is not optimal, 5) abuse of authority. In this study the authors conclude that the Local Government Pelalawan actually has made every effort to carry out development policy of Bhakti Praja Office, but should the Local Government Pelalawan should be able to run the Development Policy of Bhakti Praja office with optimal implementation.Keywords: Policy, Development, Bhakti Praja Office, Local Governmentof Pelalawan.